Corona protein impacts on alternating current biosusceptometry signal and circulation times of differently coated MnFe2O4nanoparticles - Prospero, Andre Gonçalves [UNESP] (2021)
Background: We evaluated the impacts of corona protein (CP) formation on the alternating current biosusceptometry (ACB) signal intensity and in vivo circulation times of three differently coated magnetic nanoparticles (MNP): bare, citrate-coated and bovine serum albumin-coated MNPs. Methods: We employed the ACB system, gel electrophoresis and mass spectrometry analysis. Results: Higher CP formation led to a greater reduction in the in vitro ACB signal intensity and circulation time. We found fewer proteins forming the CP for the bovine serum albumin-coated MNPs, which presented the highest circulation time in vivo among the MNPs studied. Conclusion: These data showed better biocompatibility, stability and magnetic signal uniformity in biological media for bovine serum albumin-coated MNPs than for citrate-coated MNPs and bare MNPs.